Analisa Selisih Penjualan Dalam Sistem Informasi Akuntansi Pada PT Khing Guan Sidoarjo - Tobing, Herna; Bayu , Aditya; Supriadi, Iman (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2021)
This research was executed to analyze the purpose of the difference in the nominal amount of sales between the two accounting information systems that occurred at PT Khing Guan. The data used are secondary data collected from PT Khing Guan, research and other literature. Where this research method is a qualitative case study comparatively comparing two variables, namely system A and system B which are the accounting information system used at PT Khing Guan. The result of this groundwork is the rounding applied to the total product price excluding PPN in the system which results in a difference when the total of all products sold by PT Khing Guan results in a difference amongst the nominal value in system A and the nominal value in system B. Those result may appear as profit or loss. If the nominal amount in system A is smaller than in system B, then PT Khing Guan will experience an advantage. On the other hand, if the nominal value in system A is greater than that in system B, then PT Khing Guan will suffer a loss